Successfull urban regeneration project: Gdańsk-Letnica district case study = Skuteczny projekt rewitalizacji na przykładzie dzielnicy Gdańska - Letnicy - Urbańska-Galewska, Elżbieta; Apollo, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents the process of urban regeneration of Gdansk Letnica district, a project that from a very short time perspective can be described as successful. The paper will present a brief district?s history as well as analysis of circumstances that may have influenced Gdansk authorities? decision of starting an urban regeneration project. The next part shows preparation of the urban regeneration project and its implementation. The conclusions take into account all aspects of the process, i.e. technical, economic and social.
Keywords: rewitalizacja; zarządzanie ryzykiem; inżynieria procesów budowlanych; revitalization; risk management; engineering of construction processes